Indirect land use change: review of existing models and strategies for mitigation. Issue 1 (January 2012) - Wicke, Birka; Verweij, Pita; van Meijl, Hans; van Vuuren, Detlef P; Faaij, Andre PC
This study reviews the current status, uncertainties and shortcomings of existing models of land use change (LUC) and associated GHG emissions as a result of biofuel production. The study also identifies options for improving the models and conducting further analysis. Moreover, because the extent of indirect LUC related to biofuels largely depends on other land uses, particularly agriculture, this study explores strategies for mitigating overall LUC and its effects. Despite recent improvements and refinements of the models, this review finds large uncertainties, primarily related to the underlying data and assumptions of the market-equilibrium models. Thus, there is still considerable scope for further scientific improvements of the modeling efforts. In addition, analyzing how overall LUC and its effects can be minimized is an important topic for further research and can deliver more concrete input for developing proper policy strategies. Future studies should investigate the impact of sustainability criteria and the effects of strategies for mitigating LUC, such as increasing agricultural efficiency, optimizing bioenergy production chains, using currently unused residues and byproducts, and producing feedstocks on degraded and marginal land.